Design of Digital Parity Generator Layout Using 0.7 micron Technology - Wahab Musa; Sri Wahyuni Dali; Ade Irawaty Tolago (Institute of Advanced Engineering and Science, 2018)
The proposed digital parity generator circuit is an integrated circuit functions to detect data errors at the transmitter end, and check it at the receiving end. In digital communications, the digital messages are transmitted in the form of 1’s and 0’s between two points. It is an error free if both are the same. The purpose of this research is to implement a design method of digital parity generator layout with 0.7 micron process technology ECPD07 from Tanner Tools. Layout design starts from making schematic circuit, test function and make a layout. Next, check the layout results in terms of design rules and verify the desired functionality gradually. The results show that the circuit has functioned well as an odd parity generator. The simulation results obtained with loads CL = 25 fF, tpLH = 2nS and tpHL = 1.46 nS indicate that tp = 1.73nS or operating frequency of 578 MHz. The integrated digital parity generator circuit using transmission gate has a size of 14758 um2 (78.5 um x188 um), consisting of 74 gates.